2020
DOI: 10.3390/ijerph17020466
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mechanisms of Action: Using a Testing Typology to Understand Intervention Performance in an HIV Self-Testing RCT in England and Wales

Abstract: SELPHI involves two interventions: A provides one HIV self-testing (HIVST) kit; B offers 3-monthly repeat HIVST kits if participants report ongoing risk. A logic model underpinned by the Behaviour Change Wheel informed the design of the intervention. SELPHI recruited 10,135 cis-men and trans people in England and Wales, all reporting anal sex with a man. This paper explores how the interventions were experienced and the mechanisms of action leading to impact for different groups of trial participants. In-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…All kits distributed through SELPHI were BioSure™ 2 nd generation blood based HIVSTs. Full descriptions of the interventions and theoretical underpinnings can be found in prior publications [ 19 , 23 , 24 ]. Here we present an abridged version.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All kits distributed through SELPHI were BioSure™ 2 nd generation blood based HIVSTs. Full descriptions of the interventions and theoretical underpinnings can be found in prior publications [ 19 , 23 , 24 ]. Here we present an abridged version.…”
Section: Methodsmentioning
confidence: 99%
“…The topic guide (available in additional file 2) was developed by first and second authors, adapting a previous topic guide used in a separate sub-study including cis-MSM [ 23 , 24 ]. This process focused on adapting questions and including new ones relevant to trans people.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is scope for further exploration of whether the COM-B is sufficiently attentive to diversity (e.g., in ethnicity and other demographics and employment circumstances) amongst our target audience, since the COM-B has been criticised for over-simplifying understandings of sources of behaviour and individual responses, with the potential to ignore variation in need [ 105 ]. Nevertheless, this model has been used previously in the area of sexual health and health testing uptake, for example, to explore barriers and facilitators to uptake of chlamydia testing [ 64 ] and to inform HIV prevention interventions, such as HIV self-testing programmes [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some challenges have been highlighted with relation to the application of COM-B as an overarching framework in the context of HIV testing. It has recently been proposed that a more nuanced framework of motivation may be required to examine the influence of social norms drawn from peers, community, and society and the impact of these norms on shaping engagement with HIV testing interventions [ 106 ]. In our context, anecdotal comments made by participants who took part in the health checks indicated that for many, participation was opportunistic (e.g., a health event taking place at their workplace), yet social norms within the construction industry appeared to play a key role in participants’ decisions around engagement in health behaviours more broadly (e.g., social norms, particularly among younger males, relating to alcohol or substance use, and risky sexual behaviours), as well as help-seeking behaviours (e.g., the influence of masculinity on openness about health concerns).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is evidence that HIVST may promote mutual partner testing and thus avert condomless sex between discordant partners, increase awareness of risk and incorporate safer sex practices (Lippman SA et al, 2018;Wood BR et al, 2014;Zhu X et al, 2019), as well as generally increase HIV testing frequency among MSM (Bavinton BR et al, 2013;Witzel TC, Weatherburn P, et al, 2020;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%